INTERNET ABBREVIATIONS IN MODERN ENGLISH AND UZBEK LANGUAGES - Alautdinova Kamola Shomansurovna; Uzokova Dilnoza Zoxir qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article explores the use of internet abbreviations in modern English and Uzbek languages. It examines how these abbreviations have evolved with the advent of digital communication and their impact on language use among speakers. The study utilizes a comparative analysis approach to identify similarities and differences in the usage of abbreviations in both languages.